Virtual Autism: Understanding the Effects of Excessive Screen Exposure on Cognitive and Social Development - Sarandha Sharma; Vinod Kumar Jain; Ruby Sharma (Disease and Health: Research Developments Vol. 10, 2025)
The digital age has ushered in unprecedented technological advancements, but it has also brought forth developmental challenges, one of which is “Virtual Autism”. This phenomenon refers to autism-like symptoms emerging in young children due to excessive exposure to digital screens during critical developmental years. Unlike traditional Autism Spectrum Disorder (ASD), Virtual Autism is environment-induced and often reversible with reduced screen time and increased social interactions. This paper explores the age-wise classification of symptoms of ASD and how they compare with symptoms of Virtual Autism. This study examines two cases of "virtual autism," highlighting developmental concerns linked to excessive screen exposure and limited social interaction, emphasizing early intervention and caregiver awareness for mitigating its impact. This research follows a qualitative case study approach, utilizing two purposively selected cases of children between the ages of 3 and 4 who presented with ASD-like symptoms and had a history of excessive screen exposure. The implications of Virtual Autism extend beyond childhood, affecting academic performance, emotional well-being, and social adaptability. Early detection and intervention through screen-time regulation, play-based learning, and parental guidance can help mitigate its effects. This study emphasizes the urgent need for awareness and intervention to safeguard the neurodevelopment of children in the digital age.